Marketing: The Evolution of Digital Marketing - Kuazaqui, Edmir; Lisboa, Teresinha Covas (Archives of Business Research, 2019)
The present qualitative research had the objective of presenting a study on Marketing evolution, in order to demonstrate the changes and transformations that occurred to meet market demands. Without Marketing, we would not have the products and services available on a large scale, to the detriment of regional demands and offers, guaranteeing opportunities for all those that want to develop businesses. The methodology of the study consisted in the use of bibliographical and field techniques. The marketing evolution concept was presented, from traditional to digital, from the common to the different and disruptive, and within the conception of Marketing 4.0. It was concluded that the companies are inserted in environments of great changes and transformations and that they must perceive these changes in order to accompany the new generations in relation to the digital environment and the instruments used for its operati